Tradisi Masatua Pada Keluarga Hindu - Kade Restika Dewi (Jayapangus Press, 2019)
The existence of masatua tradition has been increasingly marginalized in this modern era. Even though the tradition has enormous benefits for the growth and development of children, especially for building character. Therefore, research that examines the existence of masatua tradition especially in Hindu families is important to do. The purpose of this study was to describe the existence of masatua tradition in Hindu families in Amlapura City, describing the constraints faced by Hindu families in Amlapura City in masatua, and describing the efforts made by Hindu Families in Amlapura City to maintain the existence of masatua Tradition. This research will be conducted in Amlapura City by taking samples in the housing area (perumnas) of Karangasem Regency. The data collection method used in this study there are 3 (three) namely the questionnaire method, observation and interview. The collected data will then be analyzed. The data in this study will be analyzed using a qualitative description approach. The technique used in data analysis in this study is inductive and argumentative techniques with steps: (1) data reduction, (2) data presentation, and (3) conclusions.